2022
DOI: 10.3390/ph15010088
|View full text |Cite
|
Sign up to set email alerts
|

Mirogabalin Decreases Pain-like Behaviours and Improves Opioid and Ketamine Antinociception in a Mouse Model of Neuropathic Pain

Abstract: Neuropathic pain remains a difficult clinical challenge due to its diverse aetiology and complex pathomechanisms, which are yet to be fully understood. Despite the variety of available therapies, many patients suffer from ineffective pain relief; hence, the search for more efficacious treatments continues. The new gabapentinoid, mirogabalin has recently been approved for clinical use. Although its main mechanism of action occurs at the α2σ-1 and α2σ-2 subunits of calcium channels and is well documented, how th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…In the mouse STZ-induced model of diabetic neuropathic pain, we confirmed that mirogabalin used at the dose of 30 mg/kg was able to elevate the mechanical and heat nociceptive threshold. This finding is in line with the previously reported data from diabetic patients (e.g., [26,29]) and some limited data about its preclinical efficacy in rodent models of diabetic peripheral neuropathy (e.g., [42]), as well as chronic constriction injury [43] and spinal cord injury [44] animal models. In our research, a lower dose of mirogabalin (10 mg/kg) compared to STZ-treated control was also able to attenuate tactile allodynia in diabetic neuropathic mice but this dose did not affect the heat nociceptive threshold.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the mouse STZ-induced model of diabetic neuropathic pain, we confirmed that mirogabalin used at the dose of 30 mg/kg was able to elevate the mechanical and heat nociceptive threshold. This finding is in line with the previously reported data from diabetic patients (e.g., [26,29]) and some limited data about its preclinical efficacy in rodent models of diabetic peripheral neuropathy (e.g., [42]), as well as chronic constriction injury [43] and spinal cord injury [44] animal models. In our research, a lower dose of mirogabalin (10 mg/kg) compared to STZ-treated control was also able to attenuate tactile allodynia in diabetic neuropathic mice but this dose did not affect the heat nociceptive threshold.…”
Section: Discussionsupporting
confidence: 91%
“…Cebranopadol at the dose of 10 mg/kg was injected subcutaneously. The doses of mirogabalin and cebranopadol were selected based on the previous studies [17] and the available literature data [67]. Control animals were given an appropriate amount of vehicle (1% Tween 80).…”
Section: Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…With this feeding assay, we found that gabapentin, an analgesic administered for neuropathic pain [ 40 , 43 , 61 , 62 ], also reduced the elicited pain in the flies. Gabapentin works through inhibiting the α 2 δ-subunit of VGCCs, which is essential to synaptic transmission [ 40 , 63 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The following drugs were used in the present study: mirogabalin (M; 10, 20, 40 mg/kg, MedChemExpress, Monmouth Junction, USA), and pregabalin (10, 20, 40 mg/kg, Pfizer Inc., New York, NY, USA). The scheme of the experiments and dosages used in our current study were based on our previously published papers [ 55 , 56 , 57 ]. The drugs were dissolved in aqua pro-injection and administered intraperitoneally (i.p.).…”
Section: Methodsmentioning
confidence: 99%